The artist and the technological society: a survey of attitudes in the wake of scientific and industrial revolution - Baker, Claerwen Glenys (Rhodes University, Faculty of Humanities, Department of Fine Art, 1976)
One of the most frequently repeated questions of our time is what is art? Since we have become conditioned to the idea that ''significant art - a much overworked modern term - belongs to the revolutionary avant-garde, artists carry their search for the new at all costs into the field of non art. P.1
Keywords: Art and technology; Art, Modern -- 20th century -- History